Implementasi Projek Penguatan Profil Pelajar Pancasila pada Jenjang SMP Negeri di Kabupaten Sragen - Masdar Hilmi; Djono Djono; Suryo Ediyono (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Every implementation of a new curriculum, including the Independent Curriculum, generally brings about major changes in learning in schools. In the Independent Curriculum, the most noticeable change is that schools must implement the Pancasila Student Profile Strengthening Project. This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project and identify the obstacles encountered during its implementation at the junior high school level in Sragen Regency. This research method uses a qualitative descriptive approach with a single embedded case study approach. The research subjects are the Principal and Teachers at SMP Negeri 1 Sidoharjo and SMP Negeri 1 Sragen. The results of the study indicate that SMP Negeri 1 Sidoharjo and SMP Negeri 1 Sragen have implemented the Pancasila Student Profile Strengthening Project. SMP Negeri 1 Sidoharjo implemented it because it is a driving school while SMP Negeri 1 Sragen implemented it because it implemented the Independent Curriculum with the Changed Independent Path. The character of students in both schools improved after implementing the Pancasila Student Profile Strengthening Project. The general characters in SMP Negeri 1 Sidoharjo that emerged were mutual cooperation and creativity. The general characters seen in the Pancasila Student Profile Strengthening Project at SMP Negeri 1 Sragen were responsibility and cooperation. A number of obstacles in the Pancasila Student Profile Strengthening Project were faced by SMP Negeri 1 Sidoharjo and SMP Negeri 1 Sragen. These obstacles were in the form of time and resources in implementing the Pancasila Student Profile Strengthening Project. From the existing research results, it was concluded that the Pancasila Student Profile Strengthening Project was implemented well although obstacles still emerged. Based on this, adjustments are needed in the Pancasila Student Profile Strengthening Project or what is now a co-curricular activity in Sragen Regency.